2021
DOI: 10.29145/2021/jqm/050107
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Response to Terrorism in Pakistan: The Role of Institutions

Abstract: This study empirically estimates the fiscal consequences of terrorism in Pakistan by using annual time series data from 1984 to 2016. By employing the autoregressive distributed lag (ARDL) technique, the study has gauged the impact of terrorist incidents on two important facets of fiscal policy, namely, tax revenue and defense spending. The results reveal that terrorism has detrimental ramifications for fiscal policy in Pakistan. Specifically, on the one hand, an increase in terrorist incidents tends to bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…However, these actions remain limited, hence the negative effects. The results are in line with those found by Mukhtar & Jehan (2021). The latter showed that terrorism has a negative effect on tax revenues in Pakistan.…”
Section: Results and Discussion Of The Relationship Between The Effec...supporting
confidence: 91%
“…However, these actions remain limited, hence the negative effects. The results are in line with those found by Mukhtar & Jehan (2021). The latter showed that terrorism has a negative effect on tax revenues in Pakistan.…”
Section: Results and Discussion Of The Relationship Between The Effec...supporting
confidence: 91%